The Influence of Authentic Leadership, Organizational Identity and Employee Engagement on Job Satisfaction and Company Performance at PT. Surya Indo Plastic in Sidoarjo - Mujiono Pangestu Alam; Ida Aju Brahmasari; Ida Aju Brahma Ratih (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
Surya Indo Plastic is a pioneer company that provides exceptional quality recycled plastic food packaging for the food and beverage industry. Established in 2006 in Indonesia. The company wants to make a positive impact and contribute to protecting the environment by offering food packaging that contains 100 percent recycled plastic, which meets the highest quality and performance standards. The company works hard to accelerate the recycling of its products. Because every cup, every lid must make a difference. PT. Surya Indo Plastic is an example that packaging can be made sustainably, to prevent plastic waste from entering our environment. By raising awareness, supporting the circular economy, and encouraging individuals and companies to recycle. SIP's ambition is to provide the best quality food packaging made from sustainable recycled plastic materials while providing the best customer service. PT Surya Indo Plastic's goal is to make a difference in food packaging through innovation, responsibility, and collaboration. The purpose of this study was to determine the effect of authentic leadership, organizational identity and employee engagement on job satisfaction and company performance at PT. Surya Indo Plastic in Sidoarjo. This study uses a quantitative method with primary data sources obtained from distributing questionnaires. The population of the study were employees of PT. Surya Indo Plastic in Sidoarjo. The selection of respondents was carried out using the saturated non-probability sampling method with a total of 208 respondents. The data analysis method used descriptive analysis and SEM-PLS analysis. The results showed that the variables of authentic leadership, organizational identity and employee engagement influenced job satisfaction and company performance of PT. Surya Indo Plastic in Sidoarjo.